Waste collection routing problem: A mini-review of recent heuristic approaches and applications - LIANG, Yun-Chia (Institutional Knowledge at Singapore Management University, 2021)
The waste collection routing problem (WCRP) can be defined as a problem of designing a route to serve all of the customers (represented as nodes) with the least total traveling time or distance, served by the least number of vehicles under specific constraints, such as vehicle capacity. The relevance of WCRP is rising due to its increased waste generation and all the challenges involved in its efficient disposal. This research provides a mini-review of the latest approaches and its application in the collection and routing of waste. Several metaheuristic algorithms are reviewed, such as ant colony optimization, simulated annealing, genetic algorithm, large neighborhood search, greedy randomized adaptive search procedures, and others. Some other approaches to solve WCRP like GIS is also introduced. Finally, a performance comparison of a real-world benchmark is presented as well as future research opportunities in WCRP field.